Measuring moisture content of honey using fiber optic technique - Mohamad Ibrahim, N.; Abbas, Zulkifly; Ismail, M. A.; Muhammad Hafizi, M. H. (Faculty of Engineering, Universiti Putra Malaysia, 2012)
This study describes the application of optical fiber in measuring moisture content in honey. The determination of moisture content in honey is important because the purity of honey is mainly dependent on its moisture content. The composition of honeys depends upon the composition of nectar. In general, major composition of honey is sugar (70%-80%) which consists of fructose (35%-45%) followed by glucose (30%-35%) and sucrose (1%-3%). Besides sugar, honey also has small quantities of vitamins, minerals, proteins and amino acids. Moisture content of honey is usually e content. The measurements that can be conducted using this technique are reflection, transmission and absorbance. The measurement system in this project consists of a light source, cuvette, reflection probe, fiber optic cable and a UV-NIR spectrometer to measure the samples reflectivity, transmission and absorbance. The relationship between reflectivity and moisture content of honey was studied at different wavelengths. The relationship was used to obtain an empirical formula to predict the moisture content in honey.